HUBUNGAN ANTARA KOMPETENSI GURU AL-QURAN HADITS DENGAN PRESTASI BELAJAR PESERTA DIDIK MATA PELAJARAN AL QURAN HADITS KELAS VIII A MADRASAH TASANAWIYAH ROUDLOTUS SHOLIHIN KECAMATAN AIR HITAM KABUPATEN LAMPUNG BARAT - Hermawan Jihad Cesar (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
Abstract The Importance of Quran and Hadith in Islamic Education The Quran and Hadith are of paramount importance to Muslims, serving as the primary sources of guidance and instruction for their faith and daily lives. This significance extends to the field of education, where the study of Quran and Hadith is a core component of the curriculum, particularly in Islamic schools like MTS Al-Furqon.1. Objectives of Quran and Hadith Education:The primary objective of teaching Quran and Hadith in MTS Al-Furqon is to equip students with the necessary knowledge and skills to comprehend these sacred texts effectively. This includes:Reading and writing proficiency: Students are taught to read and write the Quran with proper tajweed (pronunciation) and calligraphy.Understanding the meaning: Emphasis is placed on understanding the core messages and teachings conveyed in the Quran and Hadith.Applying knowledge to life: Students are encouraged to apply the lessons learned from Quran and Hadith in their daily lives, fostering personal development and moral character.2. Findings on the Quran and Hadith Learning Process at MTS Al-Furqon:An analysis of the learning process at MTS Al-Furqon reveals the following:Reading ability: The majority of students (264) have a "sufficient" to "good" level of Quran reading ability.